Cardiometabolic Changes in Different Gonadal Female States Caused by Mild Hyperuricemia and Exposure to a High-Fructose Diet - J. Soutelo; Y. A. Samaniego; M. C. Fornari; C. Reyes Toso; O. J. Ponzo (International Journal of Endocrinology)
Background. The objective of this study is to observe if mild hyperuricemia and a high-fructose diet influence the cardiovascular and metabolic systems in hypogonadic female Wistar rats compared to normogonadic female rats. Methods. Fifty-six (56) adult female Wistar rats were used in the present work. Animals were divided into two groups: normogonadic (NGN) and hypogonadic (HGN). These groups were also divided into four subgroups in accordance with the treatment: control with only water (C), fructose (F), oxonic acid (OA), and fructose + oxonic acid (FOA). Lipid profile, glycemia, uric acid, and creatinine determinations were assessed. Cardiovascular changes were evaluated by measuring blood pressure, myocyte volume, fibrosis, and intima-media aortic thickness. Results. HGN rats had higher levels of total cholesterol (TC) (p<0.01) and noHDLc (p<0.01), in addition to higher levels of uric acid (p<0.05). The OA group significantly increased myocyte volume (p<0.0001) and the percentage of fibrosis as well as the group receiving FOA (p<0.001) in both gonadal conditions, being greater in the HGN group. Hypogonadic animals presented a worse lipid profile. Conclusion. Mild hyperuricemia produces hypertension together with changes in the cardiac hypertrophy, fibrosis, and increased thickness of the intima media in hypogonadic rats fed high-fructose diet.